High serum lactate level in cranial meningioma resection: A case report. (2015) - Khalil, Ayman; Mohamed, Mohamed Albagir; Kaye, Amanda Erin; Okafo, Uchenna; Dunlea, Orla; O'Brien, Declan; Lim, Chris
Highlights: Peri-operative elevated serum lactate could be a sign of high risk of morbidity among affected patients. The rise in serum lactate level can be associated with metabolic acidosis in patient with systemic hypo-perfusion. Elevation in serum lactate level during a large meningioma resection could be transient and may not result in morbidity. Abstract: Background: Peri-operative elevated serum lactate could be a sign of high risk of morbidity among affected patients. However, this finding can be self-limiting and with no consequences in some conditions. Case presentation: We present a case of transient elevated serum lactate level in a 33 year old man that underwent a cranial meningioma resection. The patient had an elevation of serum lactate levels peri-operatively, with a spontaneous gradual decline in the serum lactate five hours post-operatively. The patient had an otherwise uncomplicated post-operative course and was discharged home on the fifth post-operative day. Conclusion: Elevation in serum lactate level during a large meningioma resection could be transient and may not result in morbidity.